APLIKASI TRAP BARRIER SYSTEM (TBS) UNTUK MENANGGULANGI HAMA TIKUS PADA PERTANIAN PADI RAMAH LINGKUNGAN DI SUBAK TIMBUL DESA GADUNG SARI KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN BALI - I N. Ardika; N.N. Darmiati (Buletin Udayana Mengabdi, 2018)
Community service activities is intended to apply Trap Barrier System (TBS) to eradicate rat in riceagriculture sustainable Subak Timbul, Gadung Sari Village, District of Eastern Selemadeg, TabananRegency, Bali. The methods used in community development in Science and Technology Activities for theRegion (IbW) is: (1) Coordination and communication are participatory with farmers' groups (Subak) ecofriendlyrice farming managers to formulate a program from the planning, operational and evaluation; (2)Extension to build public perception and understanding of the innovation programs implemented; (3)Training in applied technology that applied for the community; (4) Assistance is meeting regularly andsustainably among companion with target communities to applicated and technology that are in place.Theresults obtained showed that the science and technology activities to eradicate rat through IbW program inGadung Sari Village, District of Eastern Selemadeg Tabanan Regency, Bali could take place as indicated bythe active participation and adoption of science and technology are high. Active participation in all activitiesof the members of Subak rodent pest prevention technology is quite high, amounting to 60-95%. Field miceattacks can occur at locations close to the edge of the settlement, moor, and the unfavorable environment.